Response of Growing Season Soil Carbon and Nitrogen Components to Warming and Nitrogen Addition in Marshy Meadows of the Gahai Wetland Area - LU Zhaoyang; MA Weiwei; DU Jianan; CHANG Wenhua; HE Wanpeng; LI Shuzhuo (Shuitu Baochi Xuebao, 2024)
[Objective] To examine the response characteristics of soil carbon and nitrogen fractions in alpine wetland soil to climate warming and nitrogen deposition. [Methods] Using open-top box warming (OTC) and adding exogenous nitrogen (NH4NO3) to simulate future climate warming and nitrogen deposition tests, four treatments were established, namely control (CK), warming (W), nitrogen application (N), and warming nitrogen (WN). The soil carbon and nitrogen levels were quantified after 1.5 years. [Results] (1) The utilization of the open top box warming device resulted in a notable elevation of the mean temperature at 0—20 cm soil layer by 1.126 ℃. Additionally, this intervention led to a significant decrease in the water content (SMC) and pH levels, as well as the concentrations of soil total nitrogen (TN), microbial nitrogen (MBN), ammonium nitrogen (NH4+—N), organic carbon (SOC), and dissolved organic carbon (DOC) at the 0—10 cm soil layer. Conversely, there was an observed increase in the concentration of nitrate nitrogen (NO3-—N). (2) Nitrogen application considerably lowered the contents of NH4+—N and SOC in all the soil layers, as well as those of the contents of microbial biomass carbon (MBC) and DOC in soil layers 10—20 cm deep, but increased the contents of TN, MBN, and NO3-—N. (3) The application of nitrogen through warming conditions resulted in a large rise in SMC, TN, NO3-—N, and MBC content. Conversely, it led to a significant reduction in MBN, NH4+—N, and DOC. (4) Correlation analysis showed that there was a positive correlation between soil moisture and all physicochemical factors, and soil carbon and nitrogen components were positively correlated. [Conclusion] The results indicated that the simulated warming application of nitrogen alleviated the temperature and nitrogen limitation of plant growth in the Gahai wetland, promoted the accumulation of TN, and had a greater impact on the soil microbiota biomass carbon and nitrogen, which led to the conversion of soil microbial biomass carbon and nitrogen activities and distribution characteristics.